Growth and Stress Analysis of Spontaneous Nucleation c‐Plane Bulk AlN Crystals by a PVT Method. Issue 10 (19th August 2020) - Wang, Guodong; Zhang, Lei; Wang, Yong; Shao, Yongliang; Chen, Chengmin; Liu, Guangxia; Yao, Xiaogang; Wu, Yongzhong; Hao, Xiaopeng
Abstract: AlN is a kind of promising semiconductor material for high‐efficiency optoelectronic devices and high‐power high‐frequency electronic devices. In this work, high‐quality c ‐plane AlN single crystal with low‐stress is grown on tungsten (W) substrate using a spontaneous nucleation physical vapor transport (PVT) method. Temperature field simulation and theoretical analysis provide a theoretical guide for the AlN crystals growth experiment. The hexagonal appearance c ‐plane AlN crystal is obtained with a size up to 3 mm × 3 mm. A large radial temperature gradient and suitable supersaturation lead to a low nucleation density and the growth of AlN crystal with large size, which can be used to regulate nucleation density and size of AlN crystals on W substrate. X‐ray diffraction (XRD), Raman and electron backscatter diffraction (EBSD) results confirm that the crystal is grown along the c ‐axis direction with hexagonal wurtzite structure and high crystalline quality. The Raman micro‐mapping results indicate that the grown AlN crystal has small tensile stress, close to free‐stress, and the biaxial stress decreases from interface to surface along with the increasing of crystal thickness. This work will greatly contribute to the research of AlN crystal growth on W substrate. Abstract : The theoretical and experimental basis for the regulation of nucleation density and size of AlN crystals is provided by a physical vapor transport method on W substrate. The residual stress of the as‐obtained AlN crystal decreases from interface to surface along with the increasing of crystal thickness.